2016
DOI: 10.1523/eneuro.0269-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Suppression of Mouse Prefrontal Circuits Implicated in Task Attention

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 110 publications
3
20
0
Order By: Relevance
“…We have reported that the inactivation of excitatory neurons in the medial PFC inhibits the formation and retrieval of cocaine-associated memories [54]. An application of 5-HT inhibits pyramidal neurons through the activation of several types of 5-HT receptors including 5-HT 1A [55]. Anatomically, DRN 5-HT neurons strongly innervate the PFC [23].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the inactivation of excitatory neurons in the medial PFC inhibits the formation and retrieval of cocaine-associated memories [54]. An application of 5-HT inhibits pyramidal neurons through the activation of several types of 5-HT receptors including 5-HT 1A [55]. Anatomically, DRN 5-HT neurons strongly innervate the PFC [23].…”
Section: Discussionmentioning
confidence: 99%
“…Exploitation would be governed by low tonic 5-HT in mPFC and orbitofrontal cortex, whereas exploration would be induced when 5-HT levels are high in either area. Potential cellular mechanisms for this effect have been described by Tian et al. (2016) .…”
Section: Main Textmentioning
confidence: 99%
“…The deepest layer of prefrontal cortex, layer 6, is emerging as a key player in attentional control (Zikopoulos and Barbas, 2006 ; Béhuret et al, 2015 ; Wimmer et al, 2015 ). This layer sends extensive projections to thalamic nuclei (Mercer et al, 2005 ; Watts and Thomson, 2005 ; West et al, 2006 ; Zikopoulos and Barbas, 2006 ; Thomson, 2010 ) and to local circuit interneurons in cerebral cortex (Olsen et al, 2012 ; Tian et al, 2016 ). The corticothalamic connections are critical for top-down control of attentional processes (Miller and Cohen, 2001 ; Alitto and Usrey, 2003 ; Sherman, 2007 ; Wallace and Bertrand, 2013 ) and the corticocortical connections mediate cortical gain control (Olsen et al, 2012 ; Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%